Color Perception on Mars : Life and Speculation on the Chromatic Change in the Colonization of Mars - Cuéllar, Francisco, 1994- (2020)
Would we perceive colors in a different way on Mars? Is it possible that humanity will develop color blindness while living in space because of prolonged exposure to low gravity? Such questions sparked the following research into the design of tools for Outer Space conditions. The design of the tools for past space missions give us the background of the type of materials tools have to be made out of to be useful for astronauts. But our history as space explorers was limited to the Moon surface with the Apollo missions. Now, humans are about to face the Martian surface, where conditions are entirely different. Not only physically but psychologically. Over this research, we will be discussing the reason, importance, and dangers of space exploration under the premise that we, as explorers, will have to face the most significant test humanity has faced so far as species. The first chapter contextualizes Iceland as an ideal place for space research and a test field of space exploration development. I am connecting the country's extreme characteristics with other planets to understand why this place is essential and relevant for the topic. The second chapter will deal with more technical questions and solutions as we will see the design proposal for the Icelandic space tools and the reason behind its appearance. The third chapter goes deeper into the medical aspects of the proposal and the project itself. Dealing with scientific tests and results obtained by astronauts aboard the International space station (ISS), this part will help better understand microgravity's issue to answer our initial questions.